A dangerous triangularization of conflicting values in academic publishing: ORCID, fake authors, and risks with the lack of criminalization of the creators of fake elements - Teixeira da Silva Jaime Α. (Epistēmēs Metron Logos, 2021)
The mainstream publishing establishment is under attack from multiple known and unknown forces. This is neither hyperbole nor fantasy. Many academics may believe that the main threat lies with “predatory” journals or publishers, but this is not necessarily the case because such entities are not always easy to distinguish clearly from veritable scholarly journals or publishers. Moreover, there is a gray zone that may involve both predatory and exploitative qualities. Current submission systems are not fail-safe because they allow unscholarly or fraudulent elements to register and abuse them, for example for submitting fake research or falsified peer reports, while author identification tools like ORCID are imperfect and provide a platform for similar-minded individuals to “validate” themselves. This toxic mix of tools aimed at fortifying integrity, while allowing fake authors to breed, currently without many, or any, ethical or legal repercussions will rapidly erode the entire publishing landscape if serious legal action is not taken. The creation of fake papers by fake authors will eventually trickle down into valid literature, by virtue of the fact that cited literature cannot be thoroughly vetted, even in peer review. The integrity of valid scholarly venues is thus at high risk unless suitable, strict and ethically and legally enforceable preventative measures are implemented.